Increased humoral immunity in the jejunum of diarrhoea-predominant irritable bowel syndrome associated with clinical manifestations. Issue 9 (10th September 2014) - Vicario, Maria; González-Castro, Ana M; Martínez, Cristina; Lobo, Beatriz; Pigrau, Marc; Guilarte, Mar; de Torres, Inés; Mosquera, Jose L; Fortea, Marina; Sevillano-Aguilera, César; Salvo-Romero, Eloisa; Alonso, Carmen; et al.
Abstract : Background and aims: Altered intestinal barrier is associated with immune activation and clinical symptoms in diarrhoea-predominant IBS (IBS-D). Increased mucosal antigen load may induce specific responses; however, local antibody production and its contribution to IBS aetiopathogenesis remain undefined. This study evaluated the role of humoral activity in IBS-D. Methods: A single mucosal jejunal biopsy, luminal content and blood were obtained from healthy volunteers (H; n=30) and IBS-D (n=49; Rome III criteria) participants. Intraepithelial lymphocytes, mast cells, B lymphocytes and plasma cells were studied by imaging techniques. Differential gene expression and pathway analysis were assessed by microarray and PCR techniques. Blood and luminal immunoglobulins (Igs) were quantified. Gastrointestinal symptoms, respiratory atopy and stress and depression were also recorded. Results: Patients with IBS-D showed a higher number and activation of mucosal B lymphocytes and plasma cells (p<0.05). Mast cell density was increased in patients with IBS-D (non-atopic) and in close proximity to plasma cells (p<0.05). Microarray profiling identified differential humoral activity in IBS-D, involving proliferation and activation of B lymphocytes and Igs production (p<0.001). Mucosal humoral activity was higher in IBS-D, with upregulation of germline transcripts and Ig genes (1.3-fold–1.7-fold increase; p<0.05), and increased IgG + cells and luminal IgG compared with H (p<0.05), with no differences in blood. Biological markers of humoral activity correlated positively with bowel movements, stool form and depression. Conclusions: Enhanced small bowel humoral immunity is a distinctive feature of IBS-D. Mucosal Ig production contributes to local inflammation and clinical manifestations in IBS-D.